Three Arguments for Lotteries - STONE, PETER (My University, 2010)
Philosophers and social scientists have offered a variety of arguments for making certain types of decisions by lot. This paper examines three such arguments. These arguments identify indeterminacy, fairness and incentive effects as the major reasons for using lotteries to make decisions. These arguments are central to Jon Elster?s study of lottery use, Solomonic judgments (1989), and so the paper focuses upon their treatment in this work. Upon closer examination, all three arguments have the same basic structure, in that they appeal to a single effect lotteries can have ? a sanitizing effect. Lotteries have this effect because they make possible decision-making that makes no use of reasons, whether good or bad. All arguments for or against decision-making by lot must ultimately appeal to this effect.
PUBLISHED
Keywords: Elster; Fairness; Incentives; Indeterminacy; Lotteries